The Qur’anic Exegesis and Philological Critique: Epistemic Resilience in the Age of Corpus Coranicum - M. Ridwan; Nanda Riswanda Pohan; Faruq Aziz Al Amin; Saiful Amin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study examines the epistemic resilience of the Islamic tafsīr tradition in responding to the philological and historical critiques advanced by the Corpus Coranicum project of the Berlin-Brandenburg Academy of Sciences and Humanities. By situating the Qur’an within the religious and literary context of Late Antiquity, Corpus Coranicum has significantly influenced contemporary Qur’anic studies while generating epistemological tensions with traditional Islamic scholarship. These tensions arise from differing conceptions of the Qur’an: Western philology treats it as a historical text subject to linguistic analysis, whereas tafsīr understands it as kalām Allāh, the eternal Word of God. Employing qualitative library-based research, this article analyzes selected classical and modern exegetical works through the frameworks of Jan Assmann’s cultural memory and Talal Asad’s discursive tradition. The findings demonstrate that tafsīr is not a static or defensive tradition, but one capable of adaptation, negotiation, and renewal. Three modes of epistemic response are identified—conservative, integrative, and critical-progressive—each reflecting different strategies of engagement with modern scholarship. The study concludes that such epistemic resilience allows tafsīr to maintain theological integrity while constructively engaging contemporary philological approaches, contributing to a paradigm of epistemic coexistence in Qur’anic studies.